Evaluation of physiological functions and production performance in laying hens in three different housing systems - Gaku Shoji; Ryota Tochinai; Shin-ichi Sekizawa; Masayoshi Kuwahara (Poultry Science)
In egg production management, housing systems have been one of the major issues. Although most laying hens are housed in conventional cage (CC) worldwide, alternative systems have been adopted such as enriched cage (EC) and aviary systems (AV) mainly due to concern of animal welfare of hens. To properly evaluate housing systems from production performance and welfare status, we investigated egg production, and physiological and autonomic nervous functions of hens by using a telemetry system and HRV analysis. Hens in AV showed lower productivity compared to CC and EC, and shell characteristics were quite similar between housing systems. The results also presented that egg laying rate (ELR) of EC was higher than that of CC. As physiological parameters, we continuously recorded an electrocardiogram (ECG), heart rate (HR), body temperature (BT) and locomotor activity (LA) of hens in three different housing systems by a telemetry system. Also, to evaluate autonomic nervous function of hens as a way to investigate stress and welfare of hens on poultry farms, we analyzed heart rate variability (HRV). Hens in all three groups showed the diurnal HR and LA patterns. CC and EC had also diurnal patterns of autonomic nervous functions, suggesting that parasympathetic nervous activity is predominant during dark phase. On the other hand, these diurnal patterns were unclear in hens raised in AV, which implies that AV may suppress parasympathetic nervous activity of hens during the dark phase. Therefore, AV might diminish the rest quality of hens, and lower the biological functions and recover of hens. In addition to that, hens in AV did not increase LA by quantitative analysis. It can be concluded that AV could be harmful to egg production and welfare of hen, and that EC system seems to be a more reasonable alternative option for conventional egg production from both egg productivity and animal welfare point of views.